(untitled) (International Journal of Engineering and Computer Science, 2018)
Traditional multicast routing protocol faces many issues and challenges. To deal with it many approaches differentiating the branching routers from the non-branching ones have been introduced. But these schemes that are proposed have many issues concerning to multicast management, inefficient tree construction and excessive lookups during forwarding process of unicast and multicast packet. This paper is an improvement over novel branching-router-based multicast routing protocol. Here a router is selected to share MC’s functionality, hence the overhead on MC is reduced resulting the reduction in join latency.